Edukasi Ibadah Amaliyah Untuk Meningkatkan Pemahaman Sholat Pada Anak TPQ Nurul Islam Di Dusun Besowo Timur Desa Besowo Kepung - Alifatul Khusna; Fitriani (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2022)
This research takes the theme of "Amaliyah Worship Education to Increase Understanding of Prayer in Children of TPQ Nurul Islam in East Besowo Hamlet Ds Besowo Kec Kepung Kediri". The purpose of holding this learning is that in addition to TPQ children understanding and mastering amaliyah worship, especially in terms of prayer, they are also able to implement it in their prayer practice. The type of method used in this report is the PAR method ( Participatory Action Research) is research that actively involves all relevant parties (stakeholders) in reviewing ongoing actions (where their own experiences are an issue) in order to make changes and improvements in a better direction. The result of this research activity program is to prove that the program has been able to change the learning of Islamic religious education, especially prayer learning. In addition to understanding, they have also been able to practice it in every prayer movement according to the terms and conditions.